Penggunaan Drone Untuk Survei Photogrametri Pada Pekerjaan Konstruksi - Syarifuddin; Ghofur, Abdul; Siregar, Siregar (JURNAL TEKNIK SIPIL PERTAHANAN, 2026)
A drone is an unmanned aerial vehicle equipped with sensors and cameras that can be used for documentation activities. However, drone technology has currently evolved into various applications, including aerial mapping surveys. Technological advancements have provided significant benefits, particularly in the construction industry, by enabling accurate and efficient spatial data collection for three-dimensional modeling, progress monitoring, and volume measurement. A literature review method was employed to discuss the comparison of productivity and accuracy among three different types of drones, namely the DJI Phantom 4 Pro V2, DJI Mavic 3 Enterprise + RTK, and WingtraOne Gen II. The application of photogrammetric survey technology in linear road projects is recommended to utilize portable drones equipped with PPK and/or RTK methods, with accuracy and productivity as the primary considerations. The results of this study provide insights into the optimal combination of drone platforms and geotagging methods for the effective use of photogrammetry in construction works, particularly road construction projects.